2018
DOI: 10.1590/1676-0611-bn-2017-0418
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal potential of crude extracts of Trichoderma spp.

Abstract: Antibiosis is the mechanism by which certain microorganisms respond to the presence of others, secreting compounds or metabolites capable of inhibiting or impeding their development. The crude extract of Trichoderma contains a mixture of secondary compounds, which may show antibiotic effect, and has been used for the prospect of this fungus for biological control and other industrial purposes. Faced with the increasing demand of agriculture for ecologically compatible alternatives for the management of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
2
11
0
9
Order By: Relevance
“…Similarly, Adeniyi et al (2013), evaluating the antagonistic effect of T. virens against Lt, from cashew tree inflorescence, showed total inhibition of mycelial growth of the pathogen. In view of the results obtained in this study, there is confirmation that the antagonistic action of Trichoderma isolates is intra-and interspecifically variable, corroborating the findings of Dennis and Webster (1971), Brodeur (2012) and Marques et al (2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, Adeniyi et al (2013), evaluating the antagonistic effect of T. virens against Lt, from cashew tree inflorescence, showed total inhibition of mycelial growth of the pathogen. In view of the results obtained in this study, there is confirmation that the antagonistic action of Trichoderma isolates is intra-and interspecifically variable, corroborating the findings of Dennis and Webster (1971), Brodeur (2012) and Marques et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…Levels of biological control against a target organism are intra and interspecifically variable, and this variation also occurs between isolates of antagonistic microorganisms (Dennis and Webster, 1971;Brodeur, 2012;Marques et al, 2018). In forest plants, some studies have reported satisfactory levels of biocontrol of plant pathogens both in vitro (Marques and Uesugi, 2017;Adeniyi et al, 2013, Briceño et al, 2008, Kupper et al, 2004, Mortuza and Ilag, 1999 and in vivo (Maciel et al, 2017, Sultana andGhaffar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pacheco et al (2016) evaluated the efficacy of six Trichoderma isolates to control sclerotium wilt (S. rolfsii) of common bean (Phaseolus vulgaris) and found that three of them (T. hazianum, T. longibrachiatum and T. reesei) were more efficient in reducing sclerotial germination. Marques et al (2018) isolated two strains CEN1245 and CEN1274, both belonging to the species T. brevicompactum, exhibiting a broad spectrum against S. rolfsii, C. gloesporioides, and the other disease fungi. De la Cruz-quiroz et al (2018) studied in vitro antagonistic activity in dual culture detected that T. asperellum (T2-32) strain displayed the highest capacity of inhibition against Colletotrichum gloeosporioides up to 22.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Production of soluble antifungal compounds in liquid medium. This assay followed the methodology of Marques et al (2018) with some modif ications. The different Trichoderma strains were inoculated in flasks containing 50 mL of YES medium (yeast extract, 2%; sacarose, 15%, pH = 6) adding 1 mL of 1 × 10 6 conidia mL -1 suspension.…”
Section: Production Of Volatile Antifungal Compoundsmentioning
confidence: 99%